A Simple Method for P-waves Velocity Estimation Using Pore Attributes Shape Factor and Tortuosity - Muhammad Burhannudinnur; Suryo Prakoso (Graduate Program of Syiah Kuala University, 2020)
Several researchers have arranged an approach to estimating the P-wave velocity, but none of them specifically relates to the pore attribute. Pore attributes are one of the main factors that affect pore complexity and rock quality. If P-wave velocity is influenced by the pore complexity, then it should be possible to arrange a simple relationship of P-wave velocity with the pore attribute. This study is intended to construct an empirical relationship of P-wave velocity with a combination of pore attributes, shape factor, and tortuosity (Fsτ) so that the P-wave velocity can be easily estimated. This study used two sandstone datasets from 2 different basins, which are the northern part of the West Java basin and the Kutai basin. This research shows that a simple empirical equation can be arranged to relate the P-wave velocity with Fsτ. This relationship provides a good correlation coefficient. It offers an easy and straightforward approach to estimating P-wave